An analysis of Stafford loan repayment burdens. (April 2015) - Chapman, Bruce; Lounkaew, Kiatanantha
Highlights: We estimate the probability that US students will face future loan repayment difficulties, which has not been done before for any other country. The study performs computation and presentation of repayment burden (RB) calculations in a more disaggregated way than has been done before for the US. The disaggregation illustrates how critical it is to explore RBs across the income distribution by age and sex, and between employment sectors for lawyers. It is shown that RBs are a potentially important problem for a significant minority of debtors, and could assume major difficulties for some. Abstract: There is significant unease with the state of college loans in the US, of which Stafford loans are the most common. One of the most important issues relates to the "repayment burden" (RB), the proportion of a debtor's income per period required to repay loans. RBs are fundamental to assessments of student loan systems, and must impact on debtors' consumption experience and loan default probabilities. Surprisingly, there is little evidence of the size of RBs with respect to Stafford loans and our major goal is to rectify this deficiency through the presentation of a large range of plausible calculations, for average graduates and young lawyers working in either the private or public sectors. Importantly, we are able to compare estimates of RBs at the mean of incomes with a much more useful approach using unconditional quantile estimates of incomes. The disaggregation illustrates how critical it is to explore RBs across the income distribution by age and sex, and between employment sectors for lawyers. It is shown that RBs are a potentially important problem for a significant minority of debtors, and could assume major difficulties for some.